Fingerprint Template Security: A Proposed Framework for Enhancing Fingerprint Authentication System Using Fragile Image Watermarking Technique - Iman Hazwam, Abd. Halim (2007)
The wide use of digital media in these recent days has led to an increase of digital piracy and tampering especially for biometric identification system. This research presents the concept of information hiding and one of its sub areas is called fragile image watermarking. While the biometrics techniques offer a reliable method for personal identification, the problem of security and integrity of the biometrics data is studied. This research had proposed an architectural framework that will apply information hiding method into biometric identification system. A fingerprint watermarking method has been used to hide additional information into fingerprint images by changing the least significant bit value of a random chosen pixel of the image. The embedded information can be extracted without referencing to the original image. Table and charts are presented to show the image quality of the watermarked fingerprint images comparing to the unwatermarked(original) images. The performance of the biometric identification system when using both kinds of images is also presented. The watermark payload that can be embedded into one image is then analyzed. This study can be use for image authentication especially to detect whether the image has been tampered by image processing intention such as noise addition and blurring.